Digest: A single genetic origin and a role for bone development pathways in repeated losses of flight in steamer ducks*. (27th August 2019) - Lele, Abhimanyu; Ottenburghs, Jente
Abstract: Is there evidence for convergence in the molecular mechanisms underlying the loss of flight in the avian evolutionary tree? Campagna et al. used genomic data to investigate the genetic basis of flightlessness in steamer ducks, a recently diverged clade that is polymorphic with respect to flight. They found an association between morphological changes related to flightlessness and several genes, one of which is involved in growth and bone development, providing evidence for a single genetic origin for flightlessness.